Matching of advanced undergraduate medical students’ competence profiles with the required competence profiles of their specialty of choice for postgraduate training - Lea Jebram; Sarah Prediger; Viktor Oubaid; Sigrid Harendza (BMC Medical Education, 2023)
Abstract Background Matching between undergraduate students and their chosen specialty has implications for their personal job satisfaction and performance as well as societies’ needs regarding health care quality. Knowledge regarding student-specialty fit can help improve students’ decisions and detect potential deficiencies in specific competences. In this study, we compare self-assessed competence profiles of medical students close to graduation with the competence profiles of their specialty of choice for postgraduate training. Methods Self-assessed competence profiles were collected with the modified requirement-tracking (R-Track) questionnaire from 197 final-year medical students close to graduation in 2022. To determine student-specialty fit, difference scores between students’ self-assessed competences and physicians’ requirements for specific specialties were calculated across the R-Track’s six competence areas “Motivation”, “Personality traits”, “Social interactive competences”, “Mental abilities”, “Psychomotor & multitasking abilities”, and “Sensory abilities”, which were assessed on a 5-point Likert scale (1: “very low” to 5: “very high”). Mean difference scores across competence areas were calculated and compared between specialties with multivariate analysis of variance. Student-specialty fit was also calculated independent of students’ choices. Results The competence area “Motivation” scored highest for both students and physicians across specialties. However, students’ scores were lower than physicians’ requirements for “Motivation” as well as “Personality traits” across all specialties. Difference scores for “Social interactive competences” were either close to zero or showed higher scores for students. A similar competence pattern for internal medicine, general medicine, paediatrics, and gynaecology was identified with higher than required student scores for “Mental abilities”, “Psychomotor & multitasking abilities”, and “Sensory abilities”. All other specialties showed higher physicians’ requirements for at least one of these competence areas. Independent of students’ specialty choice, we found the highest difference score in favour of student scores for general medicine (0.31) and the lowest difference score for internal medicine (-0.02). Conclusions Students’ competence profiles overall show better fit with person-oriented specialties. “Mental abilities”, “Psychomotor & multitasking abilities”, and “Sensory abilities” show higher requirement scores for more technique-oriented specialties. Students interested in such specialties could focus more on basic skill development in undergraduate training or will develop specific skills during residency.